UTILIZATION OF AI-BASED LEARNING APPLICATIONS IN IMPROVING STUDENTS' RELIGIOUS DIGITAL LITERACY - Fery Firmansyah; Herwati; Ummi Lailia Maghfiroh (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to analyze the utilization of Artificial Intelligence (AI)-based learning applications in enhancing students’ religious digital literacy at MA Model Zainul Hasan Genggong. The increasing exposure of students to digital religious content, including information that is inconsistent with Islamic values, has created an urgent need for adaptive and critical digital literacy skills in Islamic education settings. In response, AI-based learning applications are positioned as an innovative pedagogical tool that can support students in accessing, evaluating, and verifying religious information more effectively in the digital era. This research employs a qualitative approach with a case study design to explore the phenomenon in depth within its natural context. Data were collected through observation, in-depth interviews, and documentation involving teachers, students, and school stakeholders. The data were analyzed using thematic analysis to identify patterns related to the use of AI technologies in Islamic learning processes and their impact on students’ religious digital literacy. The findings reveal that AI-based learning applications contribute significantly to improving students’ engagement in learning, enhancing their ability to access and understand Islamic content, and encouraging more selective attitudes toward digital religious information. AI tools such as adaptive learning systems, educational chatbots, and verified content search applications support personalized learning experiences and help students comprehend complex religious concepts more effectively. However, the study also identifies key challenges, particularly in students’ critical literacy skills and teacher’s limited digital competencies, which affect the optimal integration of AI in Islamic education. The study concludes that AI-based learning applications play a strategic role in strengthening students’ religious digital literacy by promoting more interactive, adaptive, and learner-centered education. Nevertheless, successful implementation requires stronger teacher guidance, improved digital literacy competencies, and institutional support to ensure that AI integration aligns with Islamic educational values and pesantren-based ethical principles.